Nano-enzyme colorimetric sensor, preparation method thereof and detection of kanamycin

By combining carbon nanotubes and graphene oxide composite materials with ceria nanoparticles, N-GOs-CNTs@CeO2 nanoenzymes are formed, and the colorimetric sensor is constructed, which solves the problems of detection height limit and detection time of kanamycin residue detection in the prior art, and achieves a fast, accurate and low detection limit detection effect.

CN119757328APending Publication Date: 2025-04-04SICHUAN AGRI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411767649.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-04

Smart Images

  • Figure CN119757328A_ABST
    Figure CN119757328A_ABST
Patent Text Reader

Abstract

The invention provides a nano-enzyme colorimetric sensor, a preparation method thereof and rapid detection of kanamycin in food, and belongs to the technical field of kanamycin detection. The N-GOs-CNTs-CeO2 nano-enzyme is prepared through a simple two-time hydrothermal method, a large number of 3D open macroporous networks are formed through compounding of GO and CNT, hybridization sites and CeO2 loading sites of N atoms are greatly increased, the catalytic activity of the N-GOs-CNTs-CeO2 nano-enzyme is greatly improved, and compared with a common aptamer colorimetric sensor, the sensor constructed by the method is more economical and practical, and has a good application prospect. Moreover, the sensor is simple to synthesize, can be well stored in a natural environment and is short in detection time, so that the sensor can be applied to on-site rapid detection of a large number of samples, and the detection limit is extremely low. Meanwhile, the operability of KAN on-site rapid detection is improved, and quantitative detection of KAN residues can be realized under the condition of being separated from an ultraviolet-visible spectrophotometer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of colorimetric sensor detection, and relates to the rapid detection of kanamycin residues in food, and specifically relates to a nanoenzyme colorimetric sensor and a preparation method thereof, and the rapid detection of kanamycin residues in food. Background Art

[0002] Kanamycin (KAN) is an alkaline aminoglycoside antibiotic produced by Streptomyces Kanamyceticus. It has the ability to block protein synthesis and can treat serious infections of Gram-positive and Gram-negative bacteria. Therefore, KAN has become a commonly used veterinary drug in poultry and aquaculture. However, irrational or excessive use of KAN may cause it to remain in animal-derived foods (such as milk, honey, eggs, and meat). After KAN is ingested into the human body with food, it may cause adverse reactions such as ototoxicity and nephrotoxicity, and in severe cases may lead to renal failure and hearing loss. Excessive use of antibiotics can produce antibiotic resistance and promote the entry of resistant pathogens into the food chain. Therefore, KAN residues have become a serious public health problem worldwide.

[0003] In response to the public health risks that KAN residues may cause, China has set a maximum residue limit (MRL) of 200 μg / kg for KAN in milk, and the European Commission has also set MRLs for KAN in different foods, including 150 μg / kg for milk and 100 μg / kg for fat and muscle. In fact, it has been reported that even long-term intake of antibiotics at levels far below the reported MRL value can cause many adverse side effects in humans.

[0004] In order to detect KAN in food matrices, a variety of detection methods have been developed, such as gas chromatography (GC), capillary electrophoresis (CE), high performance liquid chromatography (HPLC), enzyme-linked immunosorbent assay (ELISA), liquid chromatography-tandem mass spectrometry (LC-MS), paper-based chip method, etc. However, these methods currently have the disadvantages of cumbersome sample pretreatment process, easy to cause environmental pollution, need for professional operation, short service life and expensive instruments. Therefore, there is an urgent need to find a cheap, fast and accurate method for detecting KAN residues in food.

[0005] Among the sensor methods, electrochemical biosensors and colorimetric sensors have been studied more. The aptamers or biomimetic materials used in electrochemical sensors are expensive, the synthesis method is complex, and the service life of the electrodes is short. Colorimetric sensors have the advantages of obvious color change, semi-quantitative detection by naked eyes, simple instrument operation, fast detection speed and easy to achieve rapid detection of a large number of samples. They are of great significance in realizing rapid on-site detection of kanamycin. However, most of the current detection methods have poor detection limits or long detection times. Therefore, it is necessary to provide a new method that can achieve rapid detection of KAN residues, shorten the detection time, and have a low detection limit.

[0006] Natural enzymes have good catalytic efficiency and substrate specificity, and play an important role in substrate conversion. However, their high cost, low stability, sensitivity to environmental conditions, and low reuse rate limit their use in the field of sensing. Nanozymes are nanomaterials with enzyme-like properties. Compared with natural enzymes, they have the advantages of low cost, adjustable catalytic activity, good stability, and convenient preparation and storage. They have received widespread attention in recent years. So far, a variety of nanomaterials have been found to have enzyme-like activities. These nanomaterials with enzyme-like activities are widely used in the fields of biosensing, disease treatment, etc. Nanomaterial-based biomimetic enzymes are receiving more and more attention as alternatives to biocatalysts.

[0007] Nano cerium (CeO2) is a rare earth metal oxide. 3+ / Ce 4+ The reversible redox state and abundant oxygen vacancies of CeO2 give CeO2 a variety of enzyme-like activities. Studies have found that CeO2 can specifically chelate with KAN. Therefore, the catalytic property of CeO2 and its chelation with KAN can be used alone to achieve quantitative detection of KAN residues without using aptamers. However, CeO2, as a nanoparticle, is prone to aggregation when used alone as a catalytic material, which reduces the number of catalytic sites and reduces the catalytic activity, thereby reducing the sensitivity of the sensor. Therefore, avoiding CeO2 aggregation and exposing more catalytic sites in CeO2 are the keys to improving the catalytic activity of CeO2. Introducing carbon materials with good dispersibility and large specific surface area into it is expected to solve this problem.

[0008] The new nanozyme-nitrogen-doped carbon material has attracted much attention due to its excellent electronic properties and high catalytic performance. Doping heteroatom nitrogen (N) into carbon materials can enhance the peroxidase mimicking activity of nanozyme-carbon materials. Carbon nanotubes (CNTs), as a carbon-based nanomaterial, have a large specific surface area due to their high aspect ratio and one-dimensional conjugated structure. However, the dispersion of CNTs has an important influence on their application feasibility. If CNTs cannot be evenly dispersed, their high performance cannot be obtained.

[0009] Graphene oxide (GO) is a graphene oxide sheet, a water-dispersible derivative with a large specific surface area and many unique properties. It is often used as a surfactant. Therefore, adding GO can minimize the entanglement between carbon nanotubes. At present, there are many studies using CNT or GO as carriers alone, but there are only a few reports on the composite of CNT and GO as carrier materials in the field of sensing. For example, Hun et al. used CNT and GO composites as carriers to load AuNPs, and used the simulated enzyme activity of AuNPs to establish an electrochemical sensor for quantitative detection of glucose. However, its detection limit was only 90μg / L, which had a high detection limit and was difficult to detect trace amounts experimentally.

[0010] For example, Junjun Lu et al. (Microchimica Acta (2024) 191: 544) proposed a colorimetric sensor that does not use an aptamer to detect kanamycin, but its detection limit is relatively high; Weizheng Wang et al. (Biosensors and Bioelectronics 218 (2022) 114774) also proposed a colorimetric sensor that does not use an aptamer to detect kanamycin, but its detection limit is also relatively high; Jing Qian et al. (Journal of Materials Chemistry B, Issue 8, 2015) used carbon nanotubes and graphene oxide to construct a colorimetric sensor to detect cholesterol, but its detection limit is relatively high; Xu Zhu et al. (Sensors & Actuators: B. Chemical 330 (2021) 129318) used cerium dioxide and aptamers to construct a colorimetric sensor, in which the aptamer needs to be incubated for 1 hour, resulting in a longer overall detection time; Rui Peng et al. (Ionics (2022) 28:451–462) used carbon nanotubes to construct an electrochemical sensor for the detection of chloramphenicol, but its detection limit was high. It can be seen that the current colorimetric sensors using aptamers have a low detection limit, but their detection time is often long; while the colorimetric sensors without aptamers have a low detection limit and poor detection effect.

[0011] Therefore, for the detection of kanamycin residues in food, how to provide a colorimetric sensor detection method that is fast, accurate, and has a low detection limit and can be used for trace kanamycin detection has become a technical problem that needs to be solved urgently. Summary of the invention

[0012] The present invention is to solve the above technical problems, thereby providing a nanozyme colorimetric sensor and a preparation method thereof and rapid detection of kanamycin residues in food. The technical purpose of the present invention is to solve the problem that the existing colorimetric sensor often has a long detection time when using an aptamer, and the problem that the existing colorimetric sensor has a high detection limit when not using an aptamer, thereby providing a nanozyme colorimetric sensor for detecting kanamycin residues in food with both short detection time and low detection limit.

[0013] The present invention first provides a method for preparing a nanozyme colorimetric sensor for rapid detection of kanamycin, comprising the following steps:

[0014] (1) dispersing carbon nanotubes in 50% (v / v) ammonia water, heating at 80° C. for 5 h, diluting the obtained dispersion with water and filtering, and washing and drying the obtained solid;

[0015] (2) mixing graphene oxide, carbon nanotubes obtained in step (1) and urea, wherein the weight ratio of graphene oxide, carbon nanotubes and urea is 6:6:1; ultrasonically dispersing in deionized water; transferring the dispersed solution to an autoclave, reacting at 180° C. for 12 h, and washing and drying the black solid obtained by the reaction to obtain N-GOs-CNTs;

[0016] (3) The N-GOs-CNTs obtained in step (2) are dispersed in deionized water and subjected to ultrasonic dispersion treatment. Subsequently, Ce(NO3)2·6H2O is fully dissolved in the above solution under stirring, and then ammonia water is added dropwise to the reaction mixture to adjust the pH to 11.0; the above reaction mixture is transferred to an autoclave, heated at 160°C for 12h, and after cooling to room temperature, the precipitate produced is collected by centrifugation, washed and dried to obtain N-GOs-CNTs@CeO2.

[0017] The colorimetric sensor we constructed using this composite material was used to detect KAN residues, with a detection limit of approximately 1.30 μg / L.

[0018] The N-GOs-CNTs@CeO2 nanozyme synthesized by the inventor has stronger catalytic activity. The detection limit of the colorimetric sensor constructed using the composite material for residual kanamycin detection can reach 1.30μg / L. The existing colorimetric sensor cannot achieve such excellent detection sensitivity when not using aptamers, and when using aptamers, its detection time is too long, which is more than 2-3 times that of the present invention.

[0019] The above preparation method provided by the inventors prepares N-GOs-CNTs@CeO2 nanozyme by a simple two-step hydrothermal method. The large number of 3D open macroporous networks formed by the composite of GO and CNT greatly increases the hybridization sites of N atoms and the loading sites of CeO2, thereby greatly improving the catalytic activity of N-GOs-CNTs@CeO2 nanozyme. The presence of N-GOs-CNTs@CeO2 nanozyme can catalyze the oxidation of TMB by H2O2 in the system, changing the color of the sample solution from transparent to blue-green; however, when KAN is present, the color becomes lighter. Based on the ability of KAN to interfere with this color change reaction, relying on the N-GOs-CNTs@CeO2 nanozyme itself, a colorimetric sensor was designed to detect KAN in two actual sample matrices by using the difference in simulated enzyme activity caused by KAN chelating CeO2 before and after. The constructed sensor is more economical and affordable than the preparation of aptamers, and is simple to synthesize. It can also be well stored in the natural environment. The detection time is short, so that the sensor can be used for on-site rapid detection of a large number of samples, and the detection limit is extremely low. At the same time, the operability of on-site rapid detection of KAN is improved, and the quantitative detection of KAN residues can be achieved without the UV-visible spectrophotometer.

[0020] Furthermore, the mass volume ratio of the carbon nanotubes to the ammonia water in step (1) is 3g:250mL.

[0021] Furthermore, the solid obtained in step (1) is washed to neutrality and dried in a vacuum at 40° C. overnight.

[0022] Furthermore, the ultrasonication time in step (2) is 2 hours.

[0023] Furthermore, the black solid obtained in step (2) was dried at 60° C. for 12 h.

[0024] Furthermore, the mass volume ratio of N-GOs-CNTs to deionized water in step (3) is 1 mg:1 mL.

[0025] Furthermore, the molar amount of Ce(NO3)2·6H2O in step (3) is 2 mmol.

[0026] Furthermore, the drying in step (3) is performed at 60° C. for 24 hours.

[0027] The second object of the present invention is to provide a nanozyme colorimetric sensor prepared by the method described above.

[0028] The third object of the present invention is to provide the application of the nanoenzyme colorimetric sensor as described above in the rapid detection of kanamycin residues in food.

[0029] The beneficial effects of the present invention are as follows:

[0030] The present invention synthesized nitrogen-doped graphene oxide carbon nanotube composite nanomaterials loaded with cerium dioxide nanoparticles (N-GOs-CNTs@CeO2). N-GOs-CNTs@CeO2 has horseradish peroxidase (HRP) activity and catalyzes the oxidation of colorless 3,3',5,5'-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H2O2), making the solution blue. When kanamycin (KAN) is added to the system, the color of the solution becomes lighter. This shows that KAN can inhibit color change in the N-GOs-CNTs@CeO2 / TMB-H2O2 system. Therefore, we developed a colorimetric sensor based on N-GOs-CNTs@CeO2 to detect KAN residues. The linear range of the sensor is 5.0-3.0×10 3 μg / L, and the detection limit was 1.30μg / L. The analysis effect of actual samples (milk and honey) was good, with a recovery rate of 96.5% to 104.8%. The constructed nanozyme colorimetric sensor has broad application prospects in food safety detection. At the same time, we constructed a smartphone-based KAN monitoring platform to further expand the application of nanozymes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Schematic diagram of the synthesis method of N-GOs-CNTs@CeO2.

[0032] Figure 2 As shown in the figure: (a) Scanning electron microscope image of CNTs after pretreatment; (b) Scanning electron microscope image of N-GOs-CNTs; (c)(d) Scanning electron microscope images of N-GOs-CNTs@CeO2; (e)-(h) Transmission electron microscope images of N-GOs-CNTs@CeO2.

[0033] Figure 3 As shown in the figure: (a) XRD spectra of N-GOs-CNTs and N-GOs-CNTs@CeO2; (b) XPS spectra of N-GOs-CNTs; (c) Raman spectra of N-GOs-CNTs and N-GOs-CNTs@CeO2.

[0034] Figure 4 They are: (a) the relationship between incubation time and the UV-visible absorption value of the N-GOs-CNTs@CeO2 / TMB-H2O2 / KAN reaction system; (b) the relationship between pH and the UV-visible absorption value of the N-GOs-CNTs@CeO2 / TMB-H2O2 reaction system; (c) the relationship between reaction temperature and the UV-visible absorption value of the N-GOs-CNTs@CeO2 / TMB-H2O2 reaction system.

[0035] Figure 5 The following are: (a), (b) the relationship between absorbance and different KAN concentrations (illustration: corresponding photos of different KAN concentrations) and the logarithmic concentration linear calibration diagram (N-GOs-CNTs@CeO2 sensor); (c), (d) the relationship between absorbance and different KAN concentrations and the logarithmic concentration linear calibration diagram (CeO2 sensor); (e) the selectivity of N-GOs-CNTs@CeO2 (illustration: test sample image); (f) the anti-interference performance of N-GOs-CNTs@CeO2 ( Inset: test sample image); (g) UV-visible absorption value of N-GOs-CNTs@CeO2 / TMB-H2O2 reaction system within 90 days; (h) Linear calibration graph of gray value and different KAN concentrations (Figure: test sample channel graph); (i) Selectivity of the sensing platform based on N-GOs-CNTs@CeO2 (Figure: test sample channel graph); (j) Anti-interference performance of the sensing platform based on N-GOs-CNTs@CeO2 (Figure: test sample channel graph). DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.

[0037] Example 1

[0038] 1. Experimental Materials and Methods

[0039] 1.1 Materials and reagents

[0040] Multi-walled carbon nanotubes (CNT), cerium nitrate, kanamycin, ciprofloxacin, tetracycline, oxytetracycline, chloramphenicol, thiamphenicol, cephalexin, streptomycin, and kanamycin were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; graphene oxide (GO) was purchased from Suzhou Carbon Graphene; urea, potassium carbonate, calcium chloride, magnesium chloride, sodium chloride, ferric chloride, potassium chloride, hydrochloric acid, citric acid, methanol, and zinc nitrate hexahydrate were purchased from Chengdu Cologne Chemicals Co., Ltd. All reagents used in the experiment were analytical or chromatographically pure unless otherwise specified, and the test water was 18.2MΩ.cm ultrapure water.

[0041] 1.2 Preparation of N-GOs-CNTs

[0042] The preparation method of N-GOs-CNTs is as follows: 0.3g CNT is dispersed in a mixed solution of 25mL ammonia water and H2O2 (v:v=1:1), and the dispersion is heated at 80℃ for 5h. The obtained dispersion is diluted with water and filtered, and then the obtained solid is rinsed to neutrality, and the sample is dried in a vacuum at 40℃ overnight. 30mg GO, 30mg CNT obtained after pretreatment and 5g urea are ultrasonically dispersed in 60mL deionized water for 2h; the well-dispersed solution is transferred to a 100mL Teflon autoclave, reacted at 180℃ for 12h, the black solid is filtered and washed with deionized water several times, and dried at 60℃ for 12h to obtain N-GOs-CNTs. 1.3 Preparation of N-GOs-CNTs@CeO2

[0043] The preparation method of N-GOs-CNTs@CeO2 is as follows: 20 mg N-GOs-CNTs is dispersed in 20 mL deionized water, ultrasonically treated for 1 h, and then 2 mmol Ce(NO3)2·6H2O is fully dissolved into the above solution by vigorous stirring, and then ammonia water is added dropwise to the reaction mixture to adjust the pH to 11.0; the above reaction mixture is transferred to a 100 mL Teflon autoclave, heated at 160°C for 12 h, and after the autoclave is cooled to room temperature, the precipitate is collected by a centrifuge, and repeatedly washed with deionized water and anhydrous ethanol; dried at 60°C for 24 h to obtain N-GOs-CNTs@CeO2.

[0044] Schematic diagram of the two-step hydrothermal method for synthesizing N-GOs-CNTs@CeO2 is shown in Figure 1 .

[0045] Scanning electron microscopy (ZEISS GeminiSEM 300, Germany) and transmission electron microscopy (FEI Tecnai G2F20, USA) were used to characterize the morphology of N-GOs-CNTs and N-GOs-CNTs@CeO2. X-ray diffractometer (Rigaku D / max-A, Japan) was used to characterize the crystal structure of N-GOs-CNTs and N-GOs-CNTs@CeO2. In addition, Raman spectroscopy was used to identify surface defects of carbon nanomaterials. XPS (X-ray photoelectron spectrometer, Thermo Scientific K-Alpha, USA) was used to verify the doping of N atoms.

[0046] 1.4 Sensor detection condition optimization and detection performance evaluation

[0047] The optimal pH and reaction temperature were selected when the absorbance was highest, and the incubation time was optimized based on the absorbance inflection point.

[0048] In KAN colorimetric detection, N-GOs-CNTs@CeO2 was prepared into a 200 mg / L detection suspension. 3 The KAN sample of 10 μg / L was mixed with the prepared N-GOs-CNTs@CeO2 suspension and gently shaken for 10 min. On this basis, TMB (10mmol / L) and 200μL H2O2 (30%) were added, incubated for 10 min, and the final solution was analyzed by UV-visible spectroscopy at 652nm. The linear relationship between absorbance and KAN concentration was established, and the linear range of the sensor was evaluated. The correlation coefficient R2 was obtained, and the detection limit of the method was calculated according to the formula LOD=3σ / k.

[0049] A series of antibiotics with a 10-fold difference in concentration and a series of interferents with a 100-fold difference in concentration were selected to evaluate the selectivity and anti-interference properties of the sensor, respectively.

[0050] 1.5 Smartphone-based Kanamycin Sensing Platform

[0051] Under the optimal detection conditions, a series of kanamycin solutions of different concentrations were added to the detection system, and pictures of the samples were taken with a smartphone (the phone was 10 cm away from the picture) for subsequent processing. The picture was opened with Image J software and a specific luminescent area was selected. Then, the area was subjected to channel separation processing to obtain three black and white pictures, corresponding to the red, green and blue channels respectively. The black and white picture corresponding to the red channel was selected, and the color threshold was adjusted to obtain the gray value, and a linear relationship between the gray value and the kanamycin concentration was established.

[0052] 1.6 Actual sample testing

[0053] Honey and milk were selected as real samples to detect the KAN concentration. For spiked honey, 1 g of honey was added to 10 mL of deionized water, a certain amount of KAN was added thereto, the mixture was filtered with a 0.22 μm filter membrane, and stored at room temperature overnight. For spiked milk, KAN was dissolved in deionized water and added to 10 mL of skim milk. The pH was adjusted to 4.6 with acetic acid (HAc, 20%, v / v) to denature and precipitate the protein at the isoelectric point. After the mixture was kept at 45°C for 30 min, the sample was centrifuged at 8000 rpm for 15 min, the supernatant was collected and diluted 100 times with deionized water, and then filtered with a 0.22 μm filter membrane for use. The skim milk filtrate with KAN added was stored in a refrigerator at 4°C for use. The above experiment needs to be repeated three times.

[0054] 2. Results and Discussion

[0055] 1. Characterization of synthetic materials

[0056] Figure 2Image a in the middle is a scanning electron microscope (SEM) image of CNTs. It can be seen that the CNTs are entangled with each other and almost ball-shaped, and their dispersion is poor. Figure 2 Figure b is a scanning electron microscope (SEM) image of N-GOs-CNTs, from which it can be seen that GO and CNTs are dispersed with each other to form an obvious three-dimensional network. Figure 2 Figures c and d are scanning electron microscope (SEM) images of N-GOs-CNTs@CeO2. It can be clearly observed that substances are loaded on the N-GOs-CNTs, forming an obvious coating on the surface of N-GOs-CNTs, and tightly combined with GO and CNT, making the surface of N-GOs-CNTs no longer smooth. Under the influence of the mutual dispersion of CNT and GO, the entire N-GOs-CNTs@CeO2 is entangled with each other and presents a large specific surface area, which greatly increases the catalytic sites on the surface of N-GOs-CNTs@CeO2.

[0057] The microstructure and structure of N-GOs-CNTs@CeO2 were further characterized by transmission electron microscopy (TEM). Figure 2 As shown. Figure 2 It can be clearly seen in a, b and c that cubic CeO2 nanoparticles with slight aggregation are loaded on the surface of thin GO and CNT. In addition, under 10 min strong ultrasonic treatment, almost no CeO2 nanoparticles fall off the surface of GO or CNT. Therefore, we believe that CeO2 nanoparticles are tightly anchored on the surface of GO or CNT. Figure 2 As shown in middle (d), the high-resolution transmission electron microscopy (HRTEM) image shows that the inter-plane spacing between the stripes is 0.289 nm, which corresponds well to the lattice of CeO2.

[0058] The crystal structure characteristics of the synthesized materials were determined by XRD. Figure 3 Figure a is the diffraction spectrum of N-GOs-CNTs and N-GOs-CNTs@CeO2. The diffraction peaks are located at 2θ=28.5°, 33.0°, 47.5°, 56.3°, 59.0°, 69.4°, 76.7°, and 79°, which are consistent with the (111), (200), (220), (311), (222), (400), (400), (311), and (420) planes of CeO2. Compared with the diffraction spectrum of N-GOs-CNTs, it shows that CeO2 grows in situ on the surface of N-GOs-CNTs to form N-GOs-CNTs@CeO2. Combined with the SEM images of N-GOs-CNTs and N-GOs-CNTs@CeO2, the diffraction peaks are located at 2θ=28.5°, 33.0°, 47.5°, 56.3°, 59.0°, 69.4°, 76.7°, and 79°, which are consistent with the (111), (200), (220), (311), (222), (400), (400), (311), and (420) planes of CeO2. Figure 2 Figures b and d further illustrate the successful preparation of N-GOs-CNTs@CeO2.

[0059] The surface chemical composition of N-GOs-CNTs was analyzed by X-ray photoelectron spectroscopy (XPS), verifying the successful doping of N atoms. Figure 3 Figure b shows a typical wide scan spectrum, which confirms that the obtained N-GO-CNTs contain C, N and O elements. This shows that N atoms are successfully doped into the GOs-CNTs composite carbon material.

[0060] The degree of graphitization can be characterized by Raman spectroscopy. Figure 3 As shown in Figure c, the G band and D band of the prepared nanocomposite material appear at 1580 cm -1 and 1346cm -1 The D band represents sp 3 Defect or disorder, G band indicates sp 2 Hybridization. In general, ID / IG can be used to evaluate the degree of disorder. The ID / IG of N-GOs-CNTs and N-GOs-CNTs@CeO2 are 2.38 and 0.96, respectively. Therefore, with the loading of CeO2, the ID / IG of the prepared nanocomposites decreases significantly, indicating a decrease in the degree of defects or disorder.

[0061] 2. Sensor detection condition optimization and detection performance evaluation

[0062] In order to achieve high-sensitivity detection of KAN, the pH, temperature and incubation time were optimized. For the incubation time, at the same KAN concentration, the incubation time was changed and the absorbance of the system was measured. The experimental results are as follows: Figure 4 As shown in a, as the incubation time increases, the absorbance decreases, and after more than 10 minutes, the absorbance changes insignificantly. Figure 4 Figure b shows the effect of pH on the catalytic performance of N-GOs-CNTs@CeO2. It can be seen that at pH 4.0, the catalytic activity of N-GOs-CNTs@CeO2 is significantly stronger, indicating that pH 4.0 is the optimal pH condition for KAN colorimetry. In addition, the effect of temperature on the absorbance of the system was also studied. Figure 4 As can be seen in figure c, at 30°C, as the temperature increases, the absorbance gradually decreases. On the one hand, this may be due to the effect of temperature on the catalytic activity of N-GOs-CNTs@CeO2, but on the other hand, there is also the effect of increased temperature on the stability of H2O2, which leads to a decrease in the amount of H2O2 used to oxidize TMB to make the system color, resulting in a decrease in absorbance. Therefore, the next experiment was carried out under the optimal conditions: pH 4.0, 30°C, and incubation time of 10 min.

[0063] Under the optimized conditions, KAN was detected by colorimetric method in acetate buffer (pH = 4.0) with different concentrations. As the concentration of KAN increased, the absorbance value gradually decreased. As KAN formed a complex with CeO2, the catalytic sites of N-GOs-CNTs@CeO2 decreased, and the absorbance decreased. 3 In the μg / L range, the absorbance and KAN concentration are logarithmically related. Figure 5 The absorbance is linearly related to the logarithm of KAN concentration ( Figure 5 (b) The corresponding regression equation is y = -0.368LogC (KAN) +2.18, and the ultralow detection limit (LOD, S / N=3) was 1.30μg / L. The results showed that a highly sensitive colorimetric detection method for KAN was successfully established through the peroxidase-like activity of N-GOs-CNTs@CeO2.

[0064] In order to verify the selectivity of the colorimetric sensor for KAN detection, this experiment also tested a variety of antibiotics such as ciprofloxacin (CIP), cephalexin (CL), streptomycin (STR), and tetracycline (TE). Figure 5 As can be seen in Figure e, the absorbance of other antibiotics at 652nm is basically the same as that of the blank, while the absorbance of KAN is significantly reduced. The results show that other antibiotics with a ten-fold difference in concentration have no obvious interference with the detection of KAN, and the method has good specificity.

[0065] At the same time, common ingredients in food matrices, such as Na + , Cl - , K + 、SO4 2- , glucose, fructose, L-lysine, citric acid, etc. were tested, and the results are shown in Figure 5 In Figure f, there is no significant difference in the absorbance of the common components in the selected food matrices at 652 nm compared with the blank, indicating that this method has good anti-interference ability.

[0066] Finally, in order to verify the stability of N-GOs-CNTs@CeO2 during long-term storage under natural conditions, enzyme activity was measured at 0d, 5d, 10d, 20d, 30d, 45d, 60d, and 90d. Figure 5 Where g is the UV-visible absorbance of the N-GOs-CNTs@CeO2 / TMB-H2O2 reaction system within 90 days. The results show that the enzyme-like activity of N-GOs-CNTs@CeO2 is lost by less than 2% during the storage period of 90 days, which indicates that the prepared N-GOs-CNTs@CeO2 has ideal storage stability, which well guarantees the excellent performance of this method.

[0067] 3. Detection performance evaluation of the KAN sensing platform based on smartphones

[0068] In order to achieve simple and rapid detection of KAN, KAN was measured using a smartphone. Figure 5 The results in h show that there is a linear correlation between KAN concentration and grayscale value, and the corresponding linear equations are grayscale value y = -18.4C (KAN) +4.51×10 4 (R2=0.987,50.0-2.00×10 3 μg / L). Based on this, the present invention successfully constructed a method for detecting KAN based on a smartphone, which expanded the application of N-GOs-CNTs@CeO2 nanozyme.

[0069] At the same time, the selectivity and anti-interference performance of the smartphone-based KAN sensing platform were evaluated. Figure 5 As can be seen from the figure, the gray value difference between other antibiotics and the blank is negligible, while the gray value of KAN is significantly reduced. The results show that other antibiotics with a ten-fold difference in concentration have no significant effect on the quantification of KAN when using a smartphone. This method can be used for the quantitative detection of KAN residues without UV-visible spectrophotometer. In addition, for anti-interference, the results are shown in Figure 5 In the figure, the difference between the grayscale value of common components in food matrix and blank is very small, indicating that when using the smartphone-based sensing platform to quantify KAN, the influence of common components in food matrix on the quantitative results can be ignored, that is, common components in food matrix have no interference with KAN quantitative results. Therefore, by evaluating the selectivity and anti-interference performance, the results show that the smartphone-based KAN sensing platform constructed by the present invention has good performance and can be applied to the quantitative detection of KAN residues in food matrix.

[0070] 4. Actual sample testing

[0071] In order to evaluate the feasibility of the two quantitative methods, the two quantitative methods were applied to the determination of KAN residues in pretreated milk and honey samples. KAN was not found in these two samples. Therefore, different doses of KAN were further added, and spike recovery experiments of the two samples were carried out. As shown in Table 1, when the UV spectrophotometer was used for quantification, the recovery rates of each experiment were between 96.5% and 104.8%, and the RSD values ​​calculated by 5 repeated measurements were all less than 6.00%; when the smartphone-based KAN sensing platform was used for quantification, the recovery rates of each experiment were between 96.5% and 104.8%, and the RSD values ​​calculated by 5 repeated measurements were all less than 6.00%. The results show that both methods have good application reliability in actual sample analysis.

[0072] Table 1 Detection results of KAN in spiked milk and honey by two methods

[0073]

[0074]

[0075] Conclusion

[0076] In summary, the present invention has developed a colorimetric sensor based on N-GOs-CNTs@CeO2. The composite of GO and CNT can not only disperse each other and inhibit their own aggregation, but also increase the specific surface area and increase the binding sites of N atoms and CeO2, thereby increasing the enzyme activity of N-GOs-CNTs@CeO2. The TMB colorimetric method was used to intuitively detect KAN in milk and honey. GO was composited with CNT by two hydrothermal methods and N atoms and CeO2 were incorporated into it. The synthesis method is simple and clear. The LOD of the constructed colorimetric sensor is 1.30μg / L, and the detection range is 3.0-5.0×10 3 μg / L. The colorimetric method is easy to visualize with the naked eye and avoids the need for complex instruments. At the same time, we constructed a method for detecting KAN based on a smartphone, which expanded the application of N-GOs-CNTs@CeO2 nanozymes. This colorimetric sensor has potential application prospects in food safety, environmental monitoring, and disease diagnosis.

[0077] Comparative Example 1

[0078] A colorimetric sensor with CeO2 as the sole material was constructed, and the basic performance of the sensor, including the linear range and detection limit, was evaluated. Figure 5 Figures c and d show the linear relationship between absorbance and KAN concentration. 2 μg / L-1.5×10 3 μg / L) increases, the absorbance of the reaction system gradually decreases (e.g. Figure 5 When the KAN concentration dropped to 1.0×10 2 μg / L and increased to 2.0×10 3 There is no obvious logarithmic relationship between concentration and absorbance at 2.1 μg / L. The detection limit of the sensor is about 28.4 μg / L.

[0079] The detection performance of two CeO2-based colorimetric sensors was compared and analyzed, and it was found that there was a significant difference in the KAN detection efficiency between CeO2 alone and the composite material. Compared with CeO2 alone, the sensor constructed using the composite material modified with N-GOs-CNTs has a wider linear range, a lower detection limit, and a better detection effect.

Claims

1. A method for preparing a nanozyme colorimetric sensor for rapid detection of kanamycin, characterized in that: The following steps are involved: (1) dispersing carbon nanotubes in 50% (v / v) ammonia water, heating at 80° C. for 5 h, diluting the obtained dispersion with water and filtering, and washing and drying the obtained solid; (2) mixing graphene oxide, carbon nanotubes obtained in step (1) and urea, wherein the weight ratio of graphene oxide, carbon nanotubes and urea is 6:6:1; ultrasonically dispersing in deionized water; transferring the dispersed solution to an autoclave, reacting at 180° C. for 12 h, and washing and drying the black solid obtained by the reaction to obtain N-GOs-CNTs; (3) The N-GOs-CNTs obtained in step (2) are dispersed in deionized water and subjected to ultrasonic dispersion treatment. Subsequently, Ce(NO3)2·6H2O is fully dissolved in the above solution under stirring, and then ammonia water is added dropwise to the reaction mixture to adjust the pH to 11.0; the above reaction mixture is transferred to an autoclave, heated at 160°C for 12h, and after cooling to room temperature, the precipitate produced is collected by centrifugation, washed and dried to obtain N-GOs-CNTs@CeO2.

2. The method according to claim 1, characterized in that The mass volume ratio of the carbon nanotubes to the ammonia water in step (1) is 3g:250mL.

3. The method according to claim 1, characterized in that The solid obtained in step (1) was washed to neutrality and dried in vacuo at 40°C overnight.

4. The method according to claim 1, characterized in that: The ultrasonic time in step (2) is 2 hours.

5. The method according to claim 1, characterized in that The black solid obtained in step (2) was dried at 60° C. for 12 h.

6. The method according to claim 1, characterized in that The mass volume ratio of N-GOs-CNTs to deionized water in step (3) is 1 mg:1 mL.

7. The method according to claim 1, characterized in that The molar amount of Ce(NO3)2·6H2O in step (3) is 2 mmol.

8. The method according to claim 1, characterized in that The drying in step (3) is performed at 60° C. for 24 hours.

9. The nanozyme colorimetric sensor prepared by the method according to any one of claims 1 to 8.

10. Use of the nanozyme colorimetric sensor according to claim 9 in rapid detection of kanamycin residues in food.

Citation Information

Patent Citations

  • Colorimetric detection method for antibiotics based on regulation and control of nano-enzyme catalytic activity by nucleic acid aptamer

    CN114324201A

  • Method for colorimetrically detecting antibiotics based on nano-enzyme hydrogel

    CN117191727A

  • SERS colorimetric biosensor for detecting uric acid based on Au / CeO2 nano-enzyme as well as construction method and application of SERS colorimetric biosensor

    CN118090704A

  • Oxygen-doped Carbon Fiber and Manufacturing Method Thereof

    KR102851864B1